A simple genetic method to distinguish mule deer and bighorn sheep fecal pellets and its application to detecting bighorn sheep colonization events in California - John Wehausen (California Fish and Wildlife Journal, 2023)
Bighorn sheep (Ovis canadensis) habitat frequently is geographically discontinuous and the metapopulation model fits this species well. Consequently, extinction-colonization dynamics are important and need to be monitored. Much of the conservation history of bighorn sheep, however, was based on a theory that natural colonization is not part of the biology of this species. That theory is not supported by a growing body of evidence that natural colonization of vacant habitat does occur in this species. Here I present a simple PCR test that distinguishes bighorn sheep fecal pellets from those of mule deer (Odocoileus hemionus) as a useful tool in documenting bighorn sheep occupancy where mule deer are present. I include examples from California of applications of this method to investigate potential colonization events.